A cestaria tradicional em Penafiel - Soeiro, Teresa (PORTVGALIA: Revista de Arqueologia do Departamento de Ciências e Técnicas do Património da Faculdade de Letras da Universidade do Porto, 2018)
The purpose of this work is to study the making of traditional basketware in Penafiel district. We attempted to trace the profession of basket making and its artisans within the background of the local crafts, since the Modern Age. We identified also the forms and know-how which are characteristic, with emphasis on the basketry products made of woven, plaited and checkered ribbon-like strips of peeled off wood, as well as the ancient manufacture of fine painted baskets of woody plant twigs. Both these handicrafts are nearing extinction.